Kam se poděly posvátné věci: Úvodní metodologický komentář z pohledu historiografie - Horský, Jan (Lidé města, 2003)
A historian has at his disposal: (1) a terminology (categories) which is defined and used in an examined source text; and (2) a terminology which is defined theoretically within the framework of modern arts. The notion of "holiness" is part of the second point, but a historian can use thus defined categories of "holiness" also when interpreting events. This category acquires importance especially in the study of cultural transformation in the 19th and 20th centuries when the ethnographically defined notion of "holiness" helps a historian in his research. First, he is not only to see in modem history just a process of individualisation of religious experience and secularisation, but, second, more important, he is to ask in which way the "holy respect" (which is an ethnographical constant) was re-thematised. However, the category of "holiness" should be used as an ideal type according to the intentions of Max Weber.